at-Tahlil Ghair at-Taqobul Litahlil al-Akhtha' - Mabruroh Mabruroh (Arabiyatuna: Jurnal Bahasa Arab, 2019)
In learning Arabic, each student will experience difficulties in the learning process. The difficulties faced by these students will affect the process of acquiring and absorbing the knowledge channeled by the instructor. Some of the effects of these difficulties are the existence of errors in understanding the rules of writing letters (Imla '), the rules of compilation of sentences (Nahwu), the process of word formation and so forth. To overcome errors in language acquisition in learning Arabic, the theory of contrastive analysis and error analysis in learning Arabic was born. Contrative analysis aims to predict the difficulties students will face in the learning process. While error analysis aims to understand the nature of errors that occur. However, in fact error analysis is the result of reflection from contrastive analysis and complementary to one another in realizing effective Arabic learning.